SOCIO-ECONOMIC JUSTICE IN THE QURAN'S PERSPECTIVE - Mujahidin Mujahidin (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
The purpose of the study is How is social justice in the perspective of the Qur'an, and how is the relationship of social justice in the perspective of the Qur'an and Pancasila. The Qur'an mentions the value of justice 78 times.2 With a variety of expressions in the Qur'an, among others, with wordsal'adl, al-qisth, andal-mizan. Al'adlwhich is called 28 times,al-qisthtried as many as 27 times, andal-mizancalled 23 times. The principle of the value of justice is an important concern in the order of human life. Research method using in this study Literature review, it is a systematic, explicit and reproducible method for identifying, evaluating and synthesizing works of research results and ideas that have been produced by researchers and practitioners. Literature review aims to make an analysis and synthesis of existing knowledge related to the topic to be researched to find empty space for research to be carried out. Result of the study Justice in WordsAl-Mizanin the Qur'an comes from the word wazan which means scales, therefore mizan is a tool for weighing. Justice in The Al-Qur'an commands to be fair in the process of law enforcement/judicial as well as threats to those who do not want to enforce the law. Justice is a basic principle in law so that Allah requires law enforcers to always punish fairly